BARITAN DANCE AS A REPRESENTATION OF THE BARITAN TRADITION OF THE BANYUWANGI COMMUNITY: TARI BARITAN SEBAGAI REPRESENTASI TRADISI BARITAN MASYARAKAT BANYUWANGI - Martha Gerryn, Lulung; Prasetyanti Sekti, Retnayu (APRON Jurnal Pemikiran Seni Pertunjukan, 2025)
The study aims to analyze the symbolic representation of the Baritan Dance created by Monica Yenike Anggraeni at the Gandrung Arum Dance Studio. The description of the Baritan Dance is elaborated through a representation analysis using Stuart Hall’s theoretical approach, supported by Susanne K. Langer’s theory of symbolic meaning, which comprises discursive and presentational symbols. This study employs a qualitative research approach, utilizing observation, interviews, and research documentation presented in the form of a narrative description. The results indicate that the Baritan Dance reveals symbolic representation of the Baritan tradition in the form of a performing art. Meanwhile, the symbolic representation of the Baritan tradition within the Baritan Dance is manifested in dance elements such as movement, musical accompaniment, costumes, and props, which serve as a means of conveying meaning to the audience. Thus, the Baritan Dance created by Monica Yenike Anggraeni at the Gandrung Arum Dance Studio is intended as a means of local cultural representation and a vehicle for preserving the Baritan tradition in Banyuwangi.